Triadelphia fusiformis sp. nov. from a freshwater habitat in Thailand - Lu, Yong-Zhong; Fan, Cui; Kang, Ji-Chuan; Liu, Jian-Kui (Jack); Hyde, Kevin D.; Boonmee, Saranyaphat; Eungwanichayapant, Prapassorn Damrongkool (Phytotaxa, 2018)
Triadelphia fusiformis sp. nov. was collected during an investigation of freshwater fungi along a north-south latitudinal gradient in the Asian region. It differs from previously described Triadelphia species in having only one form of fusiform conidia. Phylogenetic analyses based on combined ITS and LSU sequence data indicate that T. fusiformis formed a distinct subclade among the species of Triadelphia. A detailed description and illustration are provided, as well as the comparisons with similar taxa. A checklist of accepted Triadelphia species is provided.